Pembuatan Lampu Flip-Flop menggunakan Arduino Uno untuk mendukung Mata Kulaih Algoritma dan Pemrograman - Irna Tri Yuniahastuti; Ina Sunaryantiningsih; Reza Aditya Putra (Universitas Negeri Padang, 2019)
The weakness of Electrical Engineering student in understanding the programming language is the background of this research. In addition, this material has been obtained in college, because students do not yet have a comprehensive understanding of the concept application of programming languages. Futhermore, limitations of implementing course in everyday life underlie poor student understanding. In this reseach, a jobsheet was created to support the Programming Algorithm course for Electrical Engineering student at PGRI Madiun University (UNIPMA) . It contains the programming language on the microcontroller, the microcontrolled used is Arduino which is esigned for creating flif-flop lamps. On the jobsheet contains 3 projects, namely installing Arduino, flashing LED, and flip-flop lights. Jobsheet was tested validated by 2 experts, namely linguists and material experts. The result of data analysis obtained with value of 3.55 with category of the feasible to use then the jobsheet tested on students obtained the results of the assessment of the material by 80.03% with category very feasible. So it can be concluded that this practical jobsheet is usefull for students and lecturer.